Pengaruh Pendekatan Concrete Pictorial Abstract (CPA) Terhadap Pemahaman Konsep Matematika Siswa - Fatihah, Alfito; Karo-Karo, Isran Rasyid (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2025)
The low understanding of students in mathematics can lower the quality of learners and impact learning outcomes. This is caused by learning still being teacher-centered, dominated by routine questions, and using approaches that minimally support deep understanding. If this continues, it can result in students having a low understanding of mathematical concepts. This study aims to investigate the impact of the Concrete Pictorial Abstract (CPA) approach on students' understanding of mathematical concepts. This research was conducted in grade IX at SMP Negeri 8 Percut Sei Tuan during the 2025/2026 academic year. The research employed a quantitative approach with a quasi-experimental method using a Pretest–Posttest Control Group Design. The sample included 50 students, with 25 in the experimental class and 25 in the control class, selected through Cluster Random Sampling. Data on students’ understanding of mathematical concepts were collected using valid and reliable pre-test and post-test instruments. The findings revealed that the CPA approach enhanced students’ conceptual understanding compared to conventional learning. The highest achievement was observed in the classifying indicator, followed by interpreting and inferring indicators. Therefore, the CPA approach has a significant effect on students’ understanding of mathematical concepts